Cruise visitors experience in a mediterranean port of call - Agiomirgianakis, George; Andriotis, Konstantinos (My University, 2010)
This study aims to provide a better understanding on cruise travel experience by studying cruise ship passengers motivation, satisfaction and likelihood of return to the port of Heraklion (Crete, Greece). From the fi ndings, it is evident that 'exploration' and 'escape' were among the main motivations of visitors, and 'product and services' as well as 'tour pace' were signifi cant dimensions in shaping overall satisfaction levels. Nevertheless, onshore activities were restricted to sightseeing and shopping, because of the limited available time. Based on these fi ndings, relevant proposals are made in order to provide positive port experiences.
Keywords: Activities; Cruise experience; Intention to return; Motivation; Satisfaction